Role of MSMEs in Economic Growth of Tamil Nadu: A Secondary Data Analysis - Dr. N. Esakki (African Journal of Environmental Economics and Management, 2023)
Micro, Small and Medium Enterprises (MSMEs) play a pivotal role in the economic development of regional and national economies. In the context of Tamil Nadu, MSMEs have emerged as a key driver of industrial growth, employment generation, and balanced regional development. This chapter presents a comprehensive analysis of the role of MSMEs in the economic growth of Tamil Nadu using secondary data sources. The MSME sector contributes significantly to the Gross State Domestic Product (GSDP), exports, and industrial output of the state. Tamil Nadu is one of the most industrialized states in India, with a strong presence of MSMEs in sectors such as textiles, automobile components, leather, food processing, and engineering goods. The flexibility, low capital requirements, and high employment potential of MSMEs make them essential for inclusive economic growth. This study analyzes trends in MSME growth, employment generation, and sectoral contributions over time.